Myoblast proliferation during flight muscle development in Manduca sexta is unaffected by reduced neural signaling. (January 2023) - Ludwig, J. Clark; Trimmer, Barry
Abstract: In holometabolous insects, metamorphosis involves restructuring the musculature to accommodate adult-specific anatomy and behaviors. Evidence from experiments on remodeled muscles, as well as those that develop de novo, suggests that signals from the nervous system support adult muscle development by controlling myoblast proliferation rate. However, the dorsolongitudinal flight muscles (DLMs) of Manduca sexta undergo a mixed developmental program involving larval muscle fibers, and it is not known if neurons play the same role in the formation of these muscles. To address this question, we have blocked the most promising candidate pathways for neural input and examined the DLMs for changes in proliferation. Our results show that DLM development does not depend on neural activity, Hedgehog signaling, or EGF signaling. It remains to be determined how DLM growth is controlled and why neurally mediated proliferation differs between individual muscles. Highlights: Proliferation in Manduca sexta dorsolongitudinal flight muscle development does not require neural activity. Proliferation in dorsolongitudinal flight muscle development does not require Hedgehog signaling or epidermal growth factor. The signals required for dorsolongitudinal flight muscle development may differ from those of other muscles in Manduca .